LITERATURE REVIEW ON THE IMPACT OF MICROPLASTICS ON HYDROBIOTA ORGANISMS (Scientific journal of the Fergana State University, 2024)
This article provides analytical information regarding studies conducted by scientists worldwide on microplastics, their spread in the environment, sources, and their harmful effects on living organisms.